Holistic Approach for Cancer Patients: Integration of Therapeutic Gardens and Person Centered Care (Literature Review) - Ahyar Wahyudi; Listyo Yuwanto; Abdul Rofik (PT FORMOSA CENDEKIA GLOBAL, 2023)
The concept of Person Centered Care (PCC) is a revolutionary approach in the world of health care that emerged from a strong argumentative foundation. PCC firmly recognizes that patients are not simply passive objects in the care process, but have the unique potential to be actively involved in managing their own health. This is based on deep psychological theories, one of which is the